(untitled) - Fletcher, Tim D. (London, 2008)
Drawing on UNESCO's International Hydrological Programme project on this topic, Data Requirements for Integrated Urban Water Managements explores how to improve integrated urban water management, It provides guidance on the collection, validation, storage, assessment and utilization of the relevant data. The first part of this volume describes general principles for developing a monitoring programme in support of sustainable urban water management. The second part examines in detail the monitoring of individual water cycle components. Two case studies illustrating attempts to deliver an integrated monitoring system demonstrate the fundamental principles of sustainable urban water management.
Keywords: Sewerage,Municipal water supply,Hệ thống thoát nước,Cung cấp nước đô thị